Longitudinal variability in intraseasonal oscillation in the tropical mesosphere and lower thermosphere region - Rao, R. Kondala; Gurubaran, S.; Sathishkumar, S.; Sridharan, S.; Nakamura, T.; Tsuda, T.; Takahashi, H.; Batista, P.P.; Clemesha, B.R.; Buriti, R.A.; Pancheva, D.V.; Mitchell, N.J. (My University, 2009)
Simultaneous observations of mean zonal wind at 88 km obtained by the meteor radars at Cariri (7.4°S, 36.5°W) and Ascension Island (7.9°S, 14.4°W) and two medium-frequency radars at Tirunelveli (8.7°N, 77.8°E) and Pamuengpeuk (7.7°S, 107.7°E) have been used to investigate the influence of the intraseasonal variations in the lower tropospheric convective activity associated with the Madden-Julian oscillation on the longitudinal behavior of intraseasonal oscillations (ISO) of the zonal winds in the equatorial mesosphere and lower thermosphere (MLT). The ISO activity in the lower tropospheric convective activity is examined by employing outgoing long-wave radiation (OLR) as a proxy for deep convective activity occurring in the tropical lower atmosphere. The longitudinal and temporal variabilities of the ISO amplitudes in MLT zonal winds are explained in terms of the intraseasonal variabilities in the convective activity. We have also employed daily zonal wind data provided by the United Kingdom Meteorological Office (MetO) to examine the ISO activity in zonal winds at 25 pressure levels from the surface to 0.1 hPa (60 km height) over the respective radar locations.
Keywords: Lower thermosphere; Tropical mesosphere; MLT